Analisis Faktor-Faktor Yang Mempengaruhi Tingkat Underpricing Saham Pada Perusahaan Sektor Healthcare Yang Melakukan Initial Public Offering (IPO) Di Bursa Efek Indonesia Tahun 2018 - Karnila Ali; Sri Retnaning Rahayu; Ganis Delvia (Jurnal Manajemen DIVERSIFIKASI, 2024)
This study aims to study the factors that affect underpricing in IPO shares, this is intended so that companies that will go public can anticipate the risk of loss. This study tries to identify these factors in healthcare sector companies that IPO in 2018. Some factors that can affect underpricing are underwriter reputation, stock offering percentage and profitability.This study uses a quantitative type of research. The sampling technique in this study uses purposive sampling with the aim of obtaining samples that are in accordance with the purpose of the study. This study took the population of healthcare sector companies that conducted IPOs on the IDX from 2018. During 2018 there were 3 issuers in the healthcare sector that conducted IPOs on the IDX. Then it was re-selected into 2 company stocks as a research sample. The analysis used in this study used descriptive statistical data analysis and classical assumption tests. What is then tested using multiple regression analysis consisting of hypothesis test, F test and THail test from this study are: 1. Underwriter's reputation negatively affects the level of underpricing. 2. The Share Offering Percentage has a positive effect on the level of underpricing. 3. ROE profitability has a positive effect on the level of underpricing